Labyrinths of the mind. Intellectual, creative and motivational pro-file of art students - Yamila Rigo, Daiana; Donolo, Danilo; Ferrándiz García, Carmen (Anales de Psicología / Annals of Psychology, 2010)
Studies of intelligence and creativity have been considered from more general than specific positions. The unique features that both con-structs acquired in various fields disciplinary have neglected. Pursuant to this aspect, the study that we present has as objective to analyze the profile intellectual, creative and motivational of art students (N= 71). Three in-struments were used for data collection: the MIDAS -Multiple Intelligen-ces Developmental assessment Scales-, the CREA and the WPI -Work preferred Inventory-. The descriptive analysis shows, for art students, an intellectual profile space, interpersonal and intrapersonal, a medium profile of creativity and a predominance of intrinsic motivation. The carried out correlations are positive among intelligence, creativity and motivation.